EFEKTIVITAS PENDIDIKAN KESEHATAN PERKEMBANGAN JANIN DALAM MENINGKATKAN MOTIVASI IBU HAMIL UNTUK MEMBERIKAN STIMULASI SISTEM INDRA JANIN DI DESA KARANG SENTUL KABUPATEN PASURUAN: Yunitia Fitria - P, Veryudha Eka; Wahyuni, Lutfi; Fitria, Yunitia (Jurnal Kebidanan Midwiferia, 2015)
Sensory abilities or sensitivity of a baby had been there since the baby was stillin the womb. Therefore, the stimulation was important since the baby was new born, even sinve the baby was still in the womb. The stimulation could be done since the early in the form of auditory, visual, tactileand kinesthetic stimulus. Parents’motivationwas very important in the process of providing early stimulation in the fetus, because of that they need to be equipped with knowledge and skills regarding early stimulation in the fetus through health education. This study was aimed to determine the effectiveness of health education in improving maternal motivation to do the stimulation of the fetusin the village of Karang Sentul district of Gondang Wetan region of Pasuruan. Research design used was analytic experiment with quasyexperimental approach with one group pretest-posttest design. Sampling was done with saturated sampling technique. The samples in this study were 23 pregnant women. Data collection was performed by conducting pretest before giving health education, and then did the post test after giving of health education. Based on the result of crosstab between the motivation of pregnant women before and after giving health education showed significant increasing on strong motivation category from 39,1% to 100 %. Giving health education about fetus stimulation can increase the motivation of pregnant women to stimulate the fetus. So it can be interpreted that health education is effective in increasing the motivation of pregnant women to stimulate the fetus.